Domestic Violence - Simon Lapierre (Social Work and Society, 2009)
Since the 1960s, there has been growing awareness regarding the issue of domestic violence as a form of violence against women, which has been largely influenced by the work of feminist activist and scholars in North America and Europe (Dobash and Dobash 1992). Other terms have been used to describe the same phenomenon, including domestic abuse, spousal abuse, wife battering, marital violence, intimate partner violence. Though there is no doubt that this problem has existed for much more than five decades, the tendency to label it as ‘private matters’ or ‘marital disagreements’ has obscured the reality of women living with abuse in their home. At a general level, domestic violence can be defined as the means used by a man in order to assert his control and domination over his intimate partner, whether they are married or not (Mullender 1996). It can involve incidents of physical and sexual violence, as well as verbal, psychological and financial abuse. Though some of its manifestations may be associated with particular cultural or religious groups – e.g. forced marriage and honour killing in South-Asian communities – domestic violence affects women from all classes and backgrounds.